Nature Electronics - Vaughan, Owain; SpringerLink (Online service) (London : Nature Publishing Group UK : Imprint: Nature Research.)
Nature Electronics will publish both fundamental and applied research across all areas of electronics, from the study of novel phenomena and devices, to the design, construction and wider application of electronic circuits. It will also cover commercial and industrial aspects of electronics research. At its core, the journal will be concerned with the development of new technologies and understanding the impact of these developments on society. By covering the work of scientists, engineers and industry, Nature Electronics aims to provide a comprehensive picture of the field.
Keywords: Electrical engineering; Electrical Engineering